Cloning of Lipase Gene From Thermomyces langinosus into Pichia pastoris with its Original Signal Peptide - MILANI ANGGIANI; IS HELIANTI; NIKNIK NURHAYATI; ABINAWANTO ABINAWANTO (Indonesian Society for microbiology, 2017)
Lipase is one of the most important industrial enzymes, which is widely used in the preparation of food additives, cosmetics, and pharmaceutical industries. In the previous study, we have cloned synthetic Thermomyces lanuginosus lipase gene into Bacillus subtilis and Escherichia coli and resulting low expression for enzyme activity. The aim of this research was to construct the Thermomyces lanuginosus lipase (TLL) gene into Pichia pastoris vector expression with TLL original signal peptide. TLL gene was amplified by PCR and contained original signal peptide and then inserted into pPICZÎ± A between XhoI and XbaI site, and transformed into competent cell E.coli DH5Î±. From the transformant, two of positive recombinants were analyzed by sequencing analysis. As the result,both of two recombinant have a positive target gene which has lipase gene. The correct plasmid was linearized and then was transformed in Pichia pastoris X-33 by electroporation method. Thermomyces lanuginosus synthetic gene lipase has been successfully integrated into chromosome of P. pastoris X-33, which revealed by clear zones arund the colony on Yeast extract Peptone Dextrose Tributyrin (YPD.TB) plate with zeocin. The Thermomyces lanuginosus lipase had an open reading frame of 916bp encoding TLL of 314 amino acids with theoretical molecular mass of 35 kDa. The recombinant enzyme, Thermomyces lanuginosus lipase had optimal temperature at 80ËšC and optimal pH at pH 8.